Ion channel profiles of extraocular motoneurons and internuclear neurons in human abducens and trochlear nuclei - Mayadali, Ümit S.; Chertes, Christina A. M.; Sinicina, Inga; Shaikh, Aasef G.; Horn, Anja K. E. (Frontiers in Neuroanatomy, 2024)
Introduction Extraocular muscles are innervated by two anatomically and histochemically distinct motoneuron populations: motoneurons of multiply-innervated fibers (MIF), and of singly-innervated fibers (SIF). Recently, it has been established by our research group that these motoneuron types of monkey abducens and trochlear nuclei express distinct ion channel profiles: SIF motoneurons, as well as abducens internuclear neurons (INT), express strong Kv1.1 and Kv3.1b immunoreactivity, indicating their fast-firing capacity, whereas MIF motoneurons do not. Moreover, low voltage activated cation channels, such as Cav3.1 and HCN1 showed differences between MIF and SIF motoneurons, indicating distinct post-inhibitory rebound characteristics. However, the ion channel profiles of MIF and SIF motoneurons have not been established in human brainstem tissue. Methods Therefore, we used immunohistochemical methods with antibodies against Kv, Cav3 and HCN channels to (1) examine the human trochlear nucleus in terms of anatomical organization of MIF and SIF motoneurons, (2) examine immunolabeling patterns of ion channel proteins in the distinct motoneurons populations in the trochlear and abducens nuclei. Results In the examination of the trochlear nucleus, a third motoneuron subgroup was consistently encountered with weak perineuronal nets (PN). The neurons of this subgroup had -on average- larger diameters than MIF motoneurons, and smaller diameters than SIF motoneurons, and PN expression strength correlated with neuronal size. Immunolabeling of various ion channels revealed that, in general, human MIF and SIF motoneurons did not differ consistently, as opposed to the findings in monkey trochlear and abducens nuclei. Kv1.1, Kv3.1b and HCN channels were found on both MIF and SIF motoneurons and the immunolabeling density varied for multiple ion channels. On the other hand, significant differences between SIF motoneurons and INTs were found in terms of HCN1 immunoreactivity. Discussion These results indicated that motoneurons may be more variable in human in terms of histochemical and biophysiological characteristics, than previously thought. This study therefore establishes grounds for any histochemical examination of motor nuclei controlling extraocular muscles in eye movement related pathologies in the human brainstem.